2011
DOI: 10.1182/blood-2011-01-331363
|View full text |Cite
|
Sign up to set email alerts
|

DCIR-mediated enhancement of HIV-1 infection requires the ITIM-associated signal transduction pathway

Abstract: Dendritic cell immunoreceptor (DCIR) is IntroductionIt is known that cell-free virions do not efficiently cross genital epithelial cells. Instead HIV-1 uses primarily dendritic cells (DCs) to penetrate the mucosal epithelium. 1,2 The virus is then transferred and disseminated from this entry site to T-cell zones in secondary lymphoid organs, where it can productively infect residing CD4 ϩ T cells. The infection process causes a marked depletion of CD4 ϩ T cells, 3 progressive impairment of the immune system, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
(47 reference statements)
4
47
0
Order By: Relevance
“…4 supports the hypothesis that the inhibitor does not affect cellular metabolism of Raji-CD4-DCIR and Raji-CD4-DCIR-Y7F cells and DCIR inhibitor affect HIV-1 binding.) Raji-CD4-DCIR-Y7F cells have been previously described to limit HIV-1 infection in comparison with Raji-CD4-DCIR cells (Lambert et al, 2011) and result in Supplementary Fig. 5 validate that the inhibitor affect only the HIV-1 binding and attachment on Raji-CD4-DCIR.…”
Section: Impact Of the Dcir-directed Inhibitor On Exosome Release By supporting
confidence: 59%
See 1 more Smart Citation
“…4 supports the hypothesis that the inhibitor does not affect cellular metabolism of Raji-CD4-DCIR and Raji-CD4-DCIR-Y7F cells and DCIR inhibitor affect HIV-1 binding.) Raji-CD4-DCIR-Y7F cells have been previously described to limit HIV-1 infection in comparison with Raji-CD4-DCIR cells (Lambert et al, 2011) and result in Supplementary Fig. 5 validate that the inhibitor affect only the HIV-1 binding and attachment on Raji-CD4-DCIR.…”
Section: Impact Of the Dcir-directed Inhibitor On Exosome Release By supporting
confidence: 59%
“…4B). Since we already shown that inhibition of phosphatases SHP-1 and SHP-2, Src family tyrosine kinase, tyrosine kinase Syk, serine/threonine kinases PKC or MAP, significantly reduced HIV-1 binding and infection via DCIR (Lambert et al, 2011), we also pre-incubated cells with Src kinase inhibitor PP2 for 10 min before the 48 h contact with the anti-DCIR antibody. A decrease in exosome release was observed (Fig.…”
Section: Stimulation With Anti-dcir Antibody Promotes Exosome Releasementioning
confidence: 99%
“…Recent reports, which show that HIV-1-infected lymphocytes are more potent inducers of IFN-␣ than HIV-1 particles and that HIV-1 binds to BDCA-2 and DCIR, suggest that, in addition to HCV, a similar mechanism of immune evasion may be used by HIV-1. 24,[34][35][36] In view of the central role of pDCs in regulating the immune system, our results provide insight into the role of HCV-pDC interaction in HCV immune evasion and are important for our understanding of the mechanisms leading to the establishment of chronic HCV infection. …”
Section: Discussionmentioning
confidence: 87%
“…DCIR contains an inhibitory ITIM motif, and once engaged, DCIR undergoes tyrosine phosphorylation by Src kinases, leading to recruitment and activation of protein tyrosine phosphatases SHP-1 and SHP-2 and the dephosphorylation of substrates which prevent cellular activation (68,69). While the host pathways which are responsible for the induction of CHIKV-induced inflammatory disease are currently not known, DCIR has been shown to inhibit specific subsets of Toll-like receptors (53,54) and is thought to be paired with an activating CLR (DCAR) (70).…”
Section: Discussionmentioning
confidence: 99%